Pendidikan Sebagai Institusi Sosial pada Era Digital Di SMP Negeri 2 Sangatta Selatan - Ajeng Puspita Ambarsari; Muhammad Yasin (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2026)
This study aims to analyze the role of education as a social institution in the digital era at SMP Negeri 2 Sangatta Selatan. This study used a qualitative approach with data collection techniques through interviews, observation, and documentation to gain a deep understanding of the dynamics that occur in the educational process. The results show three main findings. First, education continues to function as an agent of socialization by strengthening character values, media ethics, and shaping students' social behavior, even though learning interactions have shifted to the digital realm. Second, several challenges remain, including the gap in internet access, low digital literacy among some teachers and students, and a decline in the quality of direct social interactions that have the potential to affect character formation. Third, schools respond to these challenges through various adaptive strategies, such as training to improve digital competency for teachers, the use of simple and easily accessible learning platforms, and the integration of social values ​​into digital-based learning processes. Furthermore, schools also strive to maintain a balance between online and face-to-face learning. These findings confirm that the success of educational digitalization depends heavily on the ability of educational institutions to wisely integrate technology with strengthening their social functions.